Identification and characteristics of post-traumatic stress disorder in patients with multiple sclerosis - M. T. Andreeva; T. A. Karavaeva (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2020)
The fourth edition of the Diagnostic and Statistical Manual on Mental Disorders (DSM-IV) recognizes the existence of a disease as a potential life-threatening stressor capable of causing post-traumatic stress disorder (PTSD). This research is one of the first works dedicated to the study of PTSD in patients diagnosed with «multiple sclerosis» (RS). A total of 724 complete sample patients were screened for outpatient treatment at the «City MS Center» in Saint Petersburg. According to the results of the screening survey and the expert clinical interview for the verification of the diagnosis of PTSD, the clinic—psychopathological signs sufficient for the diagnosis of PTSD have been identified in 61 patients, which is 8.4% of the total number of screened patients. The presence of PTSD is confirmed by high indices of sub-scales «avoidance», «intrusion», «physiological excitability» on the WOVTS scale, as well as higher indicators of dissociation level compared to control group. The lack of correlation between PTSD and the duration of RS, the degree of disability of patients, as well as socio-demographic data was found. Thus, the development of PTSD is more related to the premorbid personality characteristics than to the characteristics of the disease. These findings suggest that RS may have PTSD-type reactions. Further studies of the psychological characteristics of this group of patients are needed to identify the targets for psychotherapy.